The Framework for and Analysis of Good Corporate Governance Scoring in State-Owned Enterprises (SOEs): The Substance of Government Policy on Corporate Management - Dian Indri Purnamasari; Roderikus Agus Trihatmoko (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2022)
The current study aims to develop the framework for corporate governance and to assess the corporate governance scoring trend based on R-MBU/2012 in publicly traded SOEs. The study adopts mixed qualitative-quantitative methods. The qualitative method is based on grounded theory and interpreted by way of constructivist approach, whereas the quantitative method uses the technique of descriptive statistics. The data were obtained from R-MBU/2012; the sample consists of 18 SOEs listed on the Indonesia stock exchange. The results identify the relationship between variabilities in the roles of shareholders, the General Meeting of Shareholders, Board of Commissioners (BOC), Board of Directors (BOD), corporate commitment and culture, and information disclosure as the determining indicator of the level of good corporate governance implementation. Five banking companies, 2 manufacturing companies, and 3 companies in service industry are all scored ‘very good’ for the implementation of good corporate governance. However, other companies scored ‘good’, ‘fair’, and ‘poor’, respectively